Способи та засоби ідентифікації об’єктів за їх силуетами - Олексів, Максим Васильович (Національний університет "Львівська політехніка", 2012)
У дисертаційній роботі розв’язано наукову задачу підвищення ефективності візуальної ідентифікації об’єктів із складною структурою за їх силуетами на прикладі літаків. Вперше запропоновано "Спосіб автоматичної ідентифікації візуальних об’єктів за їх силуетами". Вперше запропоновано "Спосіб визначення значень коефіцієнтів рекурсії цифрових фільтрів з безконечною імпульсною характеристикою", який реалізовано у вигляді програмного пакету. Розроблено та досліджено 4 способи автоматичного виявлення та ідентифікації візуальних об’єктів за їх силуетами. Запропоновано спосіб цифрової фільтрації зображень засобами одновимірних рекурсивних фільтрів. Синтезовано та досліджено базові апаратні структури пристроїв для візуального виявлення та ідентифікації літаків. На базі запропонованих базових апаратних структур реалізовано та досліджено VHDL проекти пристроїв. Розроблено та досліджено апаратно-програмне забезпечення процесорної системи візуального виявлення та ідентифікації літаків в полі зору відеокамери. В диссертационной работе разрешена научная задача повышения эффективности визуальной идентификации объектов со сложной структурой за их силуэтами на примере самолетов. Впервые предложено "Способ автоматической идентификации визуальных объектов за их силуэтами". Впервые предложено "Способ определения значений коэффициентов рекурсии цифровых фильтров с бесконечной импульсной характеристикой", который реализован в виде программного пакета. Разработано и исследовано 4 способа автоматического обнаружения и идентификации визуальных объектов за их силуэтами. Предложен способ цифровой фильтрации изображений средствами одномерных рекурсивных фильтров. Синтезировано и исследовано базовые аппаратные структуры устройств для визуального обнаружения и идентификации самолетов. На базе предложенных базовых аппаратных структур реализовано и исследовано VHDL проекты устройств. Разработано и исследовано аппаратно-программное обеспечение процессорной системы визуального обнаружения и идентификации самолетов в поле зрения видеокамеры. The scientific task of objects with complex structure, on airplanes example, visual identification after their silhouettes improvement is solved in the PhD thesis. The method of automatic identification of visual objects after their silhouettes is suggested for the first time. The method differs from known ones by digital image filtration and binary segmentation techniques. The digital image filtration is carried out by combining high-pass and low-pass filtrations with image’s histogram equalization. This gives us an ability to allocate silhouettes of objects with complex structure with pixels with local maxima values. The binary segmentation consists of image binarization, objects pixel coordinates determination and objects, whose square is too small for correct identification, deleting. This gives us an ability to increase percent of completely separated objects. Also, the grayscale-binary segmentation technique is suggested. This technique is designed to reduce the segmentation error of the digital image in comparison with the binary segmentation. The method of digital infinite impulse response filters recursion coefficients determination is suggested for the first time. Unlike the known methods, it decreases the hardware complexity of hardware IIR filters and accumulated quantization error compared to the known structure of direct form II of IIR filters implementation. The method is software implemented. Four methods of automatic visual detection and identification of objects after their silhouettes that are based on the method of automatic identification of visual objects after their silhouettes are suggested and researched. The digital images filtration using 1-D IIR digital filters technique is suggested. Basic structures of the hardware devices for visual detection and identification of planes are synthesized and researched. VHDL projects of devices that are based on the suggested basic hardware structures are implemented and researched. The structure of a specialized digital image filtration processor is suggested for the first time. Unlike the known ones, it gives us an ability to allocate silhouettes of objects with complex structure with pixels with local maxima values even on images with low contrast. The processor filters images using 1-D IIR filters taking into account pixel’s 8-connected neighborhood with time complexity equal to O (n). Hardware and software of the airplane visual detection and identification system is implemented on basis of MC56F8367 and ADSP-BF533 microcontrollers. It is determined, that for a such system it takes approximately 9 seconds to process one 128х 128 pixels grayscale image. Processing time can be decreased using modern hardware.
Способы и средства идентификации объектов за их силуэтами
Methods and means of objects identification after their silhouettes
Keywords: цифрове опрацювання сигналів і зображень; фільтри з безконечною імпульсною характеристикою; виявлення та ідентифікація об’єктів; штучні нейронні мережі; система моніторингу; безпека пересування; спецпроцесор цифрової фільтрації зображення; цифровая обработка сигналов и изображений; фильтры с бесконечной импульсной характеристикой; обнаружение и идентификация объектов; искусственные нейронные сети; система мониторинга; безопасность передвижения; спецпроцессор цифровой фильтрации изображения; digital signal and image processing; infinite impulse response filters; infinite impulse response filters designing method; detection and identification of objects; artificial neural networks; monitoring systems; transportation safety; special purpose digital image filtering processor